Rivalry and brotherhood - Gupta, Dipankar (New Delhi, 1997)
This text demystifies the notion of the Indian peasant as being pre-colonial, and shows the astuteness with which traditions are selectively revived for contemporary purposes. By examining the specifics in the case of a rural political party in Uttar Pradesh, the author argues that by careful analysis of details, one can revise many received theories on rural movements as well as enrich the understanding of civil society, co-operatives and routine repression.
Keywords: Farmers-India-politics and government